2014
DOI: 10.18404/ijemst.61603
|View full text |Cite
|
Sign up to set email alerts
|

Primary School Students’ Spatial Orientation Strategies in an Outdoor Learning Activity supported by Mobile Technologies

Abstract: Students' different learning performance on mathematical problem solving across contexts has attracted a number of researchers' interest. The study investigates the spatial orientation ability of primary school students in an outdoor situation, where six pairs of grade six students are asked to coordinate themselves physically in terms of given distances with respect to two given points. Their spatial orientation performance is evaluated quantitatively, in terms of the number of attempts needed to reach the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
0
14
0
2
Order By: Relevance
“…One of these categories is spatial orientation. Spatial orientation is the ability to enter a given spatial situation (Liao, 2017;Peng & Sollervall, 2014;Pittalis & Christou, 2010). In spatial orientation, individuals are required to realize whether one object is to the right or left of, higher or lower than, or closer than another object.…”
Section: Introductionmentioning
confidence: 99%
“…One of these categories is spatial orientation. Spatial orientation is the ability to enter a given spatial situation (Liao, 2017;Peng & Sollervall, 2014;Pittalis & Christou, 2010). In spatial orientation, individuals are required to realize whether one object is to the right or left of, higher or lower than, or closer than another object.…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical activities presented by the RME can make the students being challenged to solve a problem. The mathematical learning with an outdoor approach can improve productive disposition towards mathematics (Peng & Sollervall, 2014). Students who did not like mathematics became happy with mathematics, after they got the RME learning.…”
Section: Introductionmentioning
confidence: 99%
“…Yenilmez and Kakmaci (2015) propose that spatial visualization skill is required in many disciplines such as Math and Geometry, Physics and Chemistry and any other work field like engineering. [3] Moreover, people use spatial ability effectively in daily life, for example in using map, exercising, and putting stuff orderly (Peng and Sollervall, 2014). [4] In National Academy of Science (2006), it is stated that there are many disciplines involve spatial ability, for instances astronomy, education, geography, geosciences, and psychology.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Moreover, people use spatial ability effectively in daily life, for example in using map, exercising, and putting stuff orderly (Peng and Sollervall, 2014). [4] In National Academy of Science (2006), it is stated that there are many disciplines involve spatial ability, for instances astronomy, education, geography, geosciences, and psychology. [5] Data found from SMAS Muhammadiyah 8 Kisaran showed that students' spatial ability was low; students found it hard to visualize components in Geometry.…”
Section: Introductionmentioning
confidence: 99%